High Actin Expression in Thrombus of Acute Ischemic Stroke Can Be a Biomarker of Atherothrombotic Origin Stroke - Wang, Rongyu; Wang, Zhiqiang; Jiang, Lianyan; Gu, Gangfeng; Zheng, Bo; Xian, Liulin; Zhang, Yaodan; Wang, Jian (Frontiers in Neurology, 2022)
Background As the treatment target, the imaging information and histologic characteristics of the thrombus may differ according to the stroke subtype. This study aimed to provide the correlative study of stroke etiology with the non-contrast CT, histological composition of retrieved clots in acute ischemic stroke (AIS). Materials and methods 94 AIS patients who underwent the endovascular treatment with successfully retrieved clots from January 2017 to October 2020 were enrolled in the present study. Histological analysis was performed using hematoxylin-eosin staining and immunostaining with CD3, CD20, CD105 and actin antibodies. CT obtained at the patients’ admission was to measure the attenuation and volume of all thrombus. Results 94 subjects were included in this study. 56 patients were classified as cardioembolic (CE), 38 were large-artery atherosclerosis (LAA). Subjects with LAA tend to exhibit higher actin, CD105 levels and lower Hounsfield Unit (HU) values than subjects with CE. After adjusting for confounders, the actin was positively correlated with CD105 but not with HU values. Logistics regression shows actin was valuable for the prediction of LAA (OR, 1.148; 95% CI, 1.075-1.227; P<0.001), even adjusted for age, sex and intervention type (OR, 1.129; 95% CI, 1.048-1.216; P=0.001), CT density and CD105 (OR, 1.161; 95% CI, 1.056-1.277; P=0.002). Actin levels have a strong accuracy in differentiating LAA from CE, especially combined with CT density and CD105, which yielded a sensitivity of 63.2%, a specificity of 89.3%, with the area under the curve at 0.821 (95% CI, 0.731-0.912). Conclusions Our findings suggest that actin's level was a major factor differentiating atherothrombotic origin strokes from the cardioembolic stroke.